Redox polymer and preparation method thereof

By using redox polymers with quaternary ammonium salt compounds or zwitterionic compounds in glucose sensors, and designing the ligand structure of metal complex X, the problems of poor water solubility and high redox equilibrium potential in the sensor are solved, and better water solubility and anti-interference ability are achieved.

CN119529185APending Publication Date: 2025-02-28SHENZHEN SISENSING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311057315.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-28

Smart Images

  • Figure CN119529185A_ABST
    Figure CN119529185A_ABST
Patent Text Reader

Abstract

The invention discloses a redox polymer and a preparation method thereof, the redox polymer has a structure as shown in the following formula (1): # imgabs0 #, A1 and A2 are the same and are selected from any one of 4-vinylpyridine and N-vinyl imidazole, and A3 is a quaternary ammonium salt compound or a zwitterionic compound. According to the present disclosure, it is possible to provide a redox polymer having better water solubility and lower redox equilibrium potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to the field of cutting-edge new materials, and more particularly to a redox polymer and a method for preparing the same. Background Art

[0002] Diabetes is a metabolic disease characterized by high blood sugar. There is currently no cure. Diabetic patients often use glucose sensors to dynamically monitor their blood sugar, which helps control the disease and monitor blood sugar in a timely manner.

[0003] Glucose sensors generally include a sensor probe and a processing device that records the sensing information. When performing dynamic blood glucose monitoring, the sensor probe is often buried under the skin of the subject. A sensing layer is provided on the working electrode of the probe. The glucose at the implanted site contacts and reacts with the sensing layer on the working electrode to generate an electrical signal. The processing device processes the electrical signal to obtain physiological parameter information associated with the blood glucose concentration level. The sensing layer on the working electrode is generally formed by dripping a sensing layer solution on the surface of the working electrode and then solidifying it. The sensing layer solution usually includes glucose enzymes and electron mediators composed of redox polymers.

[0004] However, the redox polymers used in the existing sensing layer solutions are usually poorly water-soluble, which is not conducive to drip coating, and the use of mixed solvents of organic solvents and water usually affects the enzymatic activity of glucose enzymes, which may affect the long-term stability of the working electrode. In addition, the redox equilibrium potential of the existing redox polymers is relatively high. When the working voltage is applied to the working electrode, some interfering substances in the subject's body (such as uric acid and acetaminophen, etc.) are also prone to redox reactions at higher potentials, resulting in interference with the electrical signals generated by the redox reaction of glucose molecules. Summary of the invention

[0005] The present disclosure is proposed in view of the above situation, and its purpose is to provide a redox polymer having good water solubility and low redox equilibrium potential and a preparation method thereof.

[0006] To this end, the first aspect of the present disclosure provides a redox polymer having a structure as shown in the following formula (1):

[0007]

[0008] Among them, A 1 and A 2 The same and selected from any one of 4-vinylpyridine and N-vinylimidazole, A 3 is a quaternary ammonium salt compound or a zwitterionic compound, and X has a structure shown in the following formula (2):

[0009]

[0010] Where M is a transition metal, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 It is a nitrogen-containing heterocyclic ligand, and two of them combine to form three bidentate ligands; n 1 、n 2 and n 3 The same or different and any natural number between 100 and 1000.

[0011] In the redox polymer according to the first aspect of the present disclosure, A 3 The redox polymer is configured as a quaternary ammonium salt compound or a zwitterionic compound, and can include positively charged groups and hydrophilic groups. The positively charged groups can make the surface of the redox polymer positively charged, and can form a stronger electrostatic interaction with a substance with a negative charge on the surface during specific applications. The hydrophilic groups can improve the water solubility of the redox polymer as a whole, and are convenient for applying it in a solution processing process. In addition, since X includes 6 nitrogen-containing heterocyclic ligands and they are combined in pairs to form 3 bidentate ligands, the redox polymer can also have a lower redox equilibrium potential. In this case, when the redox polymer is used as an electron mediator in a biosensor, for example, when the redox polymer is used as an electron mediator in the sensing layer of a glucose sensor, there is a stronger electrostatic interaction between the redox polymer with a positive surface charge and the glucose enzyme with a negative surface charge, which is conducive to improving the efficiency of electron transfer. The redox polymer with good water solubility can facilitate the coating process (especially the drop coating process). The low potential of the redox polymer can also make the working potential required for the glucose to contact the sensing layer to react low, thereby effectively reducing the redox reaction of high potential interferents and reducing the interference of high potential interferents with the electrical signal generated by the redox reaction of glucose molecules. Thus, a redox polymer with good water solubility and low redox equilibrium potential can be provided.

[0012] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, at least two imidazole-pyridine ligands are included in the three bidentate ligands of X. In this case, the redox polymer can have a lower redox equilibrium potential.

[0013] In the redox polymer according to the first aspect of the present disclosure, M may be osmium. This allows the redox polymer to have a lower redox equilibrium potential.

[0014] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, the zwitterionic compound is any one of sulfonate betaine, carboxylate betaine and 2-methacryloyloxyethyl phosphorylcholine. In this case, the zwitterionic compound includes both a positively charged group and a hydrophilic group, which can improve the water solubility of the redox polymer as a whole.

[0015] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, X has a structure shown in the following formula (3):

[0016]

[0017] Where, Y is a halogen ion, n 4 is any natural number from 2 to 5. In this case, the charge of the metal complex X can be balanced by the halogen ions, and the halogen ions are also hydrophilic, which can further improve the water solubility of the redox polymer.

[0018] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, X has a structure shown in the following formula (4):

[0019]

[0020] Among them, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are the same or different and are independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino. In this case, by adjusting R 1 , R 2 , R 3 , R 4 , R 5 and R 6 The substituents at the sites and the selection of imidazole-imidazole as ligands can make the redox equilibrium potential of the redox polymer within a predetermined range.

[0021] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, X has a structure shown in the following formula (5):

[0022]

[0023] Among them, R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13are the same or different and are independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino. In this case, by adjusting R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 The substituents at the sites and the selection of imidazole-pyridine as ligands can make the redox equilibrium potential of the redox polymer within a predetermined range.

[0024] In addition, in the redox polymer involved in the first aspect of the present disclosure, optionally, A 2 A is covalently bonded to X via an amide bond through dehydration condensation. 2 The connection with X has the structure shown in formula (6):

[0025]

[0026] Among them, n 5 The amide bond and A 2 The number of hydrocarbon chains between , and can be any natural number from 1 to 10; n 6 is the number of hydrocarbon chains between the amide bond and X, and is any natural number from 1 to 10. In this case, A can be increased by dehydration condensation. 2 The stability of the connection to X.

[0027] In addition, the second aspect of the present disclosure provides a method for preparing a redox polymer, comprising reacting a nitrogen-containing heterocyclic compound with a quaternary ammonium salt compound or a zwitterionic compound to generate a first polymer, wherein the nitrogen-containing heterocyclic compound is selected from any one of 4-vinylpyridine and N-vinylimidazole; and grafting a metal complex X onto the first polymer to obtain a redox polymer as shown in the following formula (1):

[0028]

[0029] Among them, A 1 and A 2 The same and selected from any one of 4-vinylpyridine and N-vinylimidazole, A 3 is the quaternary ammonium salt compound or the zwitterionic compound, and the metal complex X has a structure shown in the following formula (2):

[0030]

[0031] Where M is a transition metal, L 1 , L 2 , L 3 , L 4, L 5 and L 6 It is a nitrogen-containing heterocyclic ligand, and two of them combine to form three bidentate ligands; n 1 、n 2 and n 3 The same or different and any natural number between 100 and 1000.

[0032] In the method for preparing a redox polymer according to the second aspect of the present disclosure, A 3 The configuration is a quaternary ammonium salt compound or a zwitterionic compound, which can make the redox polymer contain positively charged groups and hydrophilic groups, wherein the positively charged groups can make the surface of the redox polymer positively charged, and can form a stronger electrostatic interaction with the substance with negative charge on the surface in specific applications; the hydrophilic group can improve the water solubility of the redox polymer as a whole, which is convenient for applying it in the process of solution processing; in addition, since X includes 6 nitrogen-containing heterocyclic ligands and two of them are combined to form 3 bidentate ligands, the redox polymer can also have a lower redox equilibrium potential. Thus, according to the preparation method disclosed in the present invention, a redox polymer with good water solubility and low redox equilibrium potential can be prepared.

[0033] According to the present disclosure, a redox polymer having good water solubility and low redox equilibrium potential and a preparation method thereof can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present disclosure will now be explained in further detail by way of example only with reference to the accompanying drawings, in which:

[0035] Figure 1 is a schematic diagram showing the usage status of the glucose monitoring probe involved in the example of the present disclosure.

[0036] Figure 2 is a schematic diagram showing the structure of a glucose monitoring probe involved in the example of the present disclosure.

[0037] Figure 3 It shows Figure 2 A schematic diagram of the structure of the glucose monitoring probe involved in a bent state.

[0038] Figure 4 Schematic diagram showing the reaction between the glucose monitoring probe and glucose involved in the example of the present disclosure.

[0039] Figure 5 is a flow chart showing a method for preparing a glucose monitoring probe according to an example of the present disclosure.

[0040] Figure 6 2 is a cyclic voltammetry graph showing the probe of Example 1 after 200 cycles.

[0041] Figure 7 FIG. 4 is a graph showing the oxidation peak current-cycle number curve of the probe of Example 1. FIG.

[0042] Figure 8 3 is a graph showing the oxidation peak current-storage days curve of the probe of Example 1.

[0043] Fig. 9 3 is a graph showing the sensitivity response of the probe of Example 1 versus glucose concentration.

[0044] Fig.10 2 is a cyclic voltammetry graph showing the probe of Example 2 after 200 cycles.

[0045] Fig.11 FIG. 4 is a graph showing the oxidation peak current-cycle number curve of the probe of Example 2.

[0046] Fig.12 3 is a graph showing the oxidation peak current-storage days curve of the probe of Example 2.

[0047] Fig.13 3 is a graph showing the sensitivity response of the probe of Example 2 versus glucose concentration.

[0048] Fig.14 is a graph showing a cyclic voltammetry curve of the probe of Example 3.

[0049] Fig.15 3 is a graph showing the sensitivity response of the probe of Example 3 versus glucose concentration.

[0050] Fig.16 is a graph showing a cyclic voltammetry curve of the probe of Example 4.

[0051] Fig.17 3 is a graph showing the sensitivity response of the probe of Example 4 versus glucose concentration.

[0052] Fig.18 is a graph showing a cyclic voltammetry curve of the probe of Comparative Example 1.

[0053] Fig.19 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 1.

[0054] Fig. 20 is a graph showing a cyclic voltammetry curve of the probe of Comparative Example 2.

[0055] Fig.21 3 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 2.

[0056] Fig. 22is a cyclic voltammetry graph showing the probe of Comparative Example 3.

[0057] Fig.23 3 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 3.

[0058] Description of reference numerals:

[0059] 1…glucose monitoring probe, 1a…connection part, 1b…implantation part, 10…working electrode, 110…sensing layer, 2…electronic system. DETAILED DESCRIPTION

[0060] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. In the following description, the same symbols are assigned to the same components, and repeated descriptions are omitted. In addition, the accompanying drawings are only schematic diagrams, and the ratio of the dimensions of the components or the shapes of the components may be different from the actual ones.

[0061] It should be noted that the terms "including" and "having" and any variations thereof in the present disclosure, such as a process, method, system, product or device that includes or has a series of steps or units, are not necessarily limited to those steps or units clearly listed, but may include or have other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0062] A biosensor is an instrument that is sensitive to biological substances and converts the concentration of the analyte into an electrical signal for detection. The biosensor obtains the sensing signal through the interaction between the analyte and the sensitive unit. The sensitive unit is usually composed of a biomolecular recognition element, which has a high specificity and affinity for the analyte. The biomolecular recognition element can be an enzyme, an antibody, a nucleic acid or a cell. The biosensor also includes an electron mediator that can convert the interaction between the sensitive unit and the analyte into a measurable electrical signal. The electron mediator can usually be a redox polymer, a semiconductor material, a metal, etc.

[0063] The first aspect of the present disclosure relates to a redox polymer having good water solubility and low redox equilibrium potential, which can be used to conduct electrons generated by the interaction between a sensitive unit and an analyte in a biosensor. For example, it can be applied to a glucose sensor, a lactate sensor, or a ketone body sensor. The redox polymer involved in the first aspect of the present disclosure can be called an electron mediator, a metal polymer, or a metal coordination polymer.

[0064] The second aspect of the present disclosure relates to a method for preparing a redox polymer. The method for preparing a redox polymer can be referred to as a preparation method or a synthesis method of a redox polymer.

[0065] The following is a detailed description of the application of the redox polymer in a glucose sensor as an example. It should be understood that although the present disclosure uses a glucose sensor as an example for detailed description, it does not mean that the redox polymer involved in the present disclosure can only be used in a glucose sensor.

[0066] In order to introduce redox polymers more clearly, the working mechanism of glucose sensors is first introduced in detail.

[0067] Figure 1 is a schematic diagram showing the usage state of the glucose monitoring probe 1 involved in the example of the present disclosure. Figure 2 is a schematic diagram showing the structure of the glucose monitoring probe 1 involved in the example of the present disclosure. Figure 3 It shows Figure 2 A schematic structural diagram of the glucose monitoring probe 1 involved in a bent state.

[0068] In some examples, the portable glucose monitor may include a glucose monitoring probe 1 and an electronic system 2 connected to the glucose monitoring probe 1 (see Figure 1 ). By implanting the glucose monitoring probe 1 of the portable glucose monitor into the human body (e.g., the surface of the human body), the glucose monitoring probe 1 can be in contact with the tissue fluid or blood on the surface of the body. Thus, the glucose monitoring probe 1 can be used to sense a sensing signal related to the glucose concentration of the body fluid, and the sensing signal can be transmitted to the electronic system 2, so that the corresponding glucose concentration can be obtained.

[0069] Specifically, a portion of the glucose monitoring probe 1 (especially the sensing portion) can be implanted, for example, on the surface of the human body and in contact with the tissue fluid in the body. In addition, another portion of the glucose monitoring probe 1 can also be connected to an electronic system 2 located outside the body surface. When the portable glucose monitor is working, the glucose monitoring probe 1 reacts with the tissue fluid or blood in the body to generate a sensing signal (such as a current signal), and transmits the sensing signal to the electronic system 2 on the body surface. The electronic system 2 processes the sensing signal to obtain the glucose concentration. Although Figure 1 The glucose monitoring probe 1 is shown as being disposed on the arm, but the embodiment is not limited thereto. For example, the glucose monitoring probe 1 may also be disposed on the abdomen, waist, legs, etc.

[0070] In some examples, the glucose monitoring probe 1 can directly detect glucose in the blood. In other examples, the glucose monitoring probe 1 can also detect glucose in tissue fluid. In this case, since the glucose concentration in tissue fluid is strongly correlated with the glucose concentration in blood, the glucose concentration in blood can also be obtained by measuring the glucose concentration in tissue fluid.

[0071] In some examples, the glucose monitoring probe 1 may include a working electrode 10 (see Figure 2 In some examples, for convenience of description, the glucose monitoring probe 1 can be divided into a connecting portion 1a and an implanting portion 1b (see Figure 3 ). Figure 3 The straight line A-A' in the figure roughly shows the dividing line that divides the glucose monitoring probe 1 into a connecting part 1a and an implanting part 1b. Specifically, when the glucose monitoring probe 1 is implanted into the body surface, the connecting part 1a can be located outside the body surface, and the implanting part 1b can be implanted inside the body surface.

[0072] In some examples, the implantable portion 1b of the glucose monitoring probe 1 may include a working electrode 10 (see Figure 2 and Figure 3 ).

[0073] In some examples, the working electrode 10 may include a sensing layer 110 (see Figure 2 ). The analyte level can be detected by the sensing layer 110. In some examples, the working electrode 10 may include a substrate layer. In some examples, the sensing layer 110 may be formed by coating a sensing layer solution on the substrate layer. In some examples, the sensing layer solution may be formed into the sensing layer 110 by at least one process such as spin coating, dip coating, drop coating, or spray coating.

[0074] In some examples, the sensing layer solution can be dripped on the working electrode 10 in the form of multiple discrete points to form the sensing layer 110. In some examples, multiple discrete points constitute the sensing layer 110. In some examples, multiple points with overlapping edges can also be dripped on the working electrode 10 to form a sensing layer 110 in which multiple points are connected in a line. In this case, it is convenient to set more sensing layer solutions on the working electrode 10, which can help improve the sensitivity of the working electrode 10.

[0075] In some examples, the sensing layer solution may include a redox polymer. In some examples, the sensing layer solution may include a glucose enzyme. The glucose enzyme may be a glucose oxidase or a glucose dehydrogenase.

[0076] Figure 4 Schematic diagram showing the reaction between the glucose monitoring probe 1 and glucose involved in the example of the present disclosure.

[0077] The following, combined Figure 4 , to GO X The reaction occurring in the sensing layer 110 of the working electrode 10 is explained by taking FAD as glucose oxidase and MED as a redox polymer as an example.

[0078] In the sensing layer 110 of the working electrode 10, when GOX When (FAD) encounters glucose in tissues, the following reactions occur:

[0079] Glucose + GOx(FAD) → Gluconolactone + GOx(FADH 2 )……Reaction formula (I)

[0080] GOx(FADH 2 )+MED ox →GOx(FAD)+MED red ……Reaction formula (II)

[0081]

[0082] In the above reaction process, it can be seen that in the chemical reaction, glucose is oxidized by glucose oxidase GOx (FAD) to generate gluconolactone and reduced glucose oxidase GOx (FADH 2 )(reaction formula (I)); reduced glucose oxidase GOx (FADH 2 ) and oxidized redox polymer MED ox Reaction to generate reduced redox polymer MED red , while reducing glucose oxidase GOx (FADH 2 ) is oxidized to glucose oxidase GOx(FAD) (reaction formula (II)); by applying a working voltage to the working electrode 10, the reduced redox polymer MED red Oxidized to the oxidized redox polymer MED ox , and electrons are generated at the same time (reaction formula (III)).

[0083] Through the above reaction formula (I) to reaction formula (III), the reaction between the sensing layer 110 and glucose can be continuously carried out. It should be noted that, Figure 4 The reaction process between the sensing layer 110 and glucose is only schematically shown, and does not mean that the structure of the sensing layer 110 disclosed in the present invention can only be used with Figure 4 The same as Figure 4 This should not be construed as limiting the structure of the sensing layer 110 of the present disclosure.

[0084] In some examples, as described above, the probe 1 may include a working electrode 10 , and a sensing layer 110 may be disposed on the working electrode 10 .

[0085] In some examples, the sensing layer 110 may include glucose enzyme. The glucose enzyme may be glucose oxidase or glucose dehydrogenase.

[0086] In some examples, a redox polymer can be used in the probe 1. Specifically, the redox polymer can be disposed in the sensing layer 110 as an electron mediator. In other words, the sensing layer 110 can include a redox polymer. In some examples, the redox polymer can have a low redox equilibrium potential (hereinafter referred to as the redox equilibrium potential). In this case, the redox polymer containing a low potential in the sensing layer 110 can reduce the working voltage required for the working electrode 10 to work properly, thereby reducing the interference of the current generated by the electrochemical reaction of the electroactive substances under some high voltages on the working electrode 10. In other words, by providing a low potential redox polymer on the sensing layer 110, it is possible to play an anti-interference role against high potential interferers.

[0087] In some examples, the potential of the redox polymer may be -100 mV to 100 mV. In some examples, the high potential interferer refers to an interfering substance with an oxidation potential greater than 100 mV. For example, the high potential interferer may include uric acid, acetaminophen, ibuprofen, acetylsalicylic acid, and the like.

[0088] It is understandable that the probability of a substance with a potential of 150 mV reacting when the working voltage is 0 mV to 100 mV is much lower than the probability of reacting when the working voltage is 100 mV to 200 mV. Therefore, generally, the lower the potential of the redox polymer, the stronger the anti-interference effect against high potential interfering substances.

[0089] In some examples, preferably, the potential of the redox polymer may be -50 mV to 50 mV. When the potential of the redox polymer is -50 mV to 50 mV, the working electrode 10 has a more significant anti-interference effect on high potential interferers such as uric acid, acetaminophen, ibuprofen and acetylsalicylic acid.

[0090] Hereinafter, the specific structure of the redox polymer will be described in detail.

[0091] In some examples, the redox polymer may have a structure as shown in formula (1):

[0092]

[0093] In some examples, A 1 and A 2 It can be a nitrogen-containing heterocyclic compound. In some examples, A 1 and A 2 Can be selected from any one of pyridine derivatives and imidazole derivatives. In some examples, A 1 and A 2 Can be selected from any one of 4-vinylpyridine and N-vinylimidazole.1 and A 2 In some examples, n 1 It can be any natural number between 100 and 1000. For example, n 1 It can be 100, 300, 500, 700, 900, or 1000. In some examples, n 2 It can be any natural number between 100 and 1000. For example, n 2 It can be 100, 300, 500, 700, 900, or 1000. In some examples, n 1 and n 2 Can be the same or different.

[0094] In some examples, X may be a metal complex (hereinafter referred to as X). In some examples, X may have a structure as shown in the following formula (2):

[0095]

[0096] In some examples, M may be a transition metal. In some examples, M may be selected from any one of osmium, nickel, chromium, iridium, and ruthenium. In some examples, M may be osmium.

[0097] In some examples, X may have six ligands. In some examples, in the chemical structure examples where X includes multiple ligands, the dotted line shown in formula (2) represents the coordination bond formed between the ligand and M. In some examples, the six ligands may be L 1 , L 2 , L 3 , L 4 , L 5 and L 6 In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 can be the same or different. In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 It may be any one of a nitrogen-containing heterocyclic ring, a halogen atom, a water molecule, an ammonia molecule, or a carbon monoxide molecule. In this case, by changing the type of the ligand, the redox equilibrium potential of the redox polymer can be made to be within a predetermined range.

[0098] In some examples, L 1 , L 2 , L 3 , L4 , L 5 and L 6 It can be a nitrogen-containing heterocyclic ligand. In this case, a coordination bond can be formed between the nitrogen atom in the ligand and M, further enhancing the binding energy between the ligand and M, thereby improving the stability of the chemical structure of the metal complex X.

[0099] In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 It can be selected from any one of pyridine derivatives and imidazole derivatives. In this case, by changing the type and composition of the ligand in the metal complex X, the redox equilibrium potential of the redox polymer can be changed, and the redox equilibrium potential of the redox polymer can be made within a predetermined range by screening.

[0100] In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 can be independently selected from any one of pyridine, imidazole, pyrimidine, thiazole and pyrrole. In some examples, preferably, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 can be independently selected from any one of pyridine and imidazole. 1 , L 2 , L 3 , L 4 , L 5 and L 6 Free groups may be included. In some examples, the free groups may be amino groups or carboxyl groups.

[0101] In some examples, X may include a monoligand and / or a bidentate ligand. “X may include a monoligand and / or a bidentate ligand” means that X may include a monoligand, X may include both a monoligand and a bidentate ligand, and X may include a bidentate ligand. Specifically, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 Can be single ligand, L 1 , L 2 , L 3 , L4 , L 5 and L 6 Any two adjacent ligands in the molecule can also combine to form a bidentate ligand.

[0102] In some examples, a bidentate ligand may be a ligand containing two coordinating atoms in one ligand. In some examples, a monodentate ligand may be a ligand containing one coordinating atom in one ligand.

[0103] In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 can combine in pairs to form bidentate ligands. In some examples, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 Three bidentate ligands can be formed by combining two of them. In this case, by changing the number of bidentate ligands in the ligand, the redox equilibrium potential of the redox polymer can be within a predetermined range.

[0104] In some examples, X may include an imidazole-pyridine ligand. For example, X may include 1, 2, or 3 imidazole-pyridine ligands. In this case, the potential of the redox polymer can be adjusted by changing the number of bidentate ligands in the ligand.

[0105] In some examples, X may include at least two imidazole-pyridine ligands. In other words, at least two imidazole-pyridine ligands are included in the three bidentate ligands of X. In this case, the redox polymer can have a lower redox equilibrium potential, so that the working potential required for glucose to contact and react with the sensing layer 110 on the working electrode 10 is lower, thereby effectively reducing the redox reaction of high-potential interferents and reducing the interference of high-potential interferents on the electrical signal generated by the redox reaction of glucose molecules.

[0106] In some examples, X may have a structure as shown in formula (3):

[0107]

[0108] In some examples, Y may be a halogen ion. In some examples, the halogen ion may be selected from any one of a fluoride ion, a chloride ion, a bromide ion, or an iodide ion. In this case, the halogen ion can balance the charge of the metal complex X, and the halogen ion is hydrophilic, which can further improve the water solubility of the redox polymer.

[0109] In some examples, n 4 It can be any natural number from 2 to 5. For example, n 4 Can be 2, 3, 4 or 5.

[0110] In some examples, X may have a structure as shown in formula (4):

[0111]

[0112] In some examples, as shown in formula (4), X may include an imidazole-imidazole ligand, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 It can be a substituent at different positions on the imidazole-imidazole ligand. In some examples, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 Can be the same or different.

[0113] In some examples, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 can be independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino. 1 can be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino, R 2 can be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino, R 3 can be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino, R 4 can be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino, R 5 can be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino, R 6 It may be selected from hydrogen, methyl, methoxy, trifluoromethyl or amino.

[0114] In this case, by adjusting R 1 , R 2 , R 3 , R 4 , R 5 and R 6 The substituents at the sites and the selection of imidazole-imidazole as ligands can make the redox equilibrium potential of the redox polymer within a predetermined range.

[0115] In some examples, X may have a structure as shown in formula (5):

[0116]

[0117] In some examples, as shown in formula (5), X may include an imidazole-pyridine ligand, R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 It can be a substituent at different positions on the imidazole-pyridine ligand. In some examples, R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 can be the same or different. In some examples, R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 can be independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino. In this case, by adjusting R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 The substituents at the sites and the selection of imidazole-pyridine as ligands can make the redox equilibrium potential of the redox polymer within a predetermined range.

[0118] In some examples, in the example where X includes multiple imidazole-pyridine ligands, the structure and group selection shown in formula (5) can be referred to, and the substituents on each imidazole-pyridine ligand can be the same or different.

[0119] In some examples, X can be grafted to A 2 In some examples, A 2 A chemical reaction occurs between X and X to form a functional group, which then grafts X onto A. 2 In this case, by 2 The way of forming functional groups with X can improve A 2 The stability of the connection with X, thereby improving the overall stability of the redox polymer.

[0120] In some examples, X and A2 In some examples, X and A can be covalently bonded by dehydration condensation. 2 It can be bonded via an amide bond or an ester bond. In some examples, preferably, X and A 2 It can be combined through amide bonds. In this case, dehydration condensation can increase A 2 The stability of the connection to X.

[0121] In some examples, X and A 2 The connection can have the structure shown in formula (6):

[0122]

[0123] In some examples, n 5 It can be an amide bond with A 2 In some examples, n 6 is the number of hydrocarbon chains between the amide bond and X. In some examples, n 5 It can be any natural number from 1 to 10. For example, n 5 It can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. In some examples, n 6 It can be any natural number from 1 to 10. For example, n 6 It can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. In some examples, n 5 and n 6 Can be the same or different.

[0124] In other examples, X and A 2 Linkage may be via a disubstituted triazole group.

[0125] In some examples, the redox polymer can be a random copolymer. In some examples, a random copolymer is a polymer formed by random copolymerization of two or more different monomers, wherein the polymerization positions of the monomers are random and the arrangement of the monomers in the structure of the random copolymer is disordered. In some examples, the random copolymer has no obvious repeating units or structural units.

[0126] In this case, A 1 , A 2 and A 3 In the polymerization reaction, A 1 , A 2 and A 3 The n in the chemical structure shown in formula (1) can be connected in any order. 1 、n 2 、n 3 It only means that the main chain of the redox polymer includes n 1 A1 and n 2 A 2 and n 3 A 3 , monomer A in the main chain 1 , A 2 and A 3 That is, formula (1) does not mean that the redox polymer can only be connected in order. 1 A 1 With n 2 A 2 With n 3 A 3 Sequential copolymerization connection, n 1 A 1 With n 2 A 2 With n 3 A 3 Can be connected randomly, for example, can be connected according to 1 A 1 With n 3 A 3 With n 2 A 2 and (n 1 -1) A 1 Sequential copolymerization and connection can also be carried out according to the 6 A 3 With n 1 A 1 With n 2 A 2 and (n 3 -6) A 3 Sequential copolymerization and connection can also be carried out according to n 2 A 2 With n 3 A 3 With n 1 A 1 Sequential copolymerization connection.

[0127] In some examples, the main chain of the redox polymer may have a structure as shown in Formula (7):

[0128]

[0129] In some examples, X can be attached to the main chain of the polymer. When X is attached to the main chain of the polymer, the main chain of the polymer needs to be modified. 1 and A 2 are selected from the same monomer, and when the modification is performed, the monomer to be modified is A to which X can be connected 2 That is, A 2 Grafted with metal complex X, A 1 The metal complex X is not grafted.

[0130] In some examples, A 3 In this case, the surface of the redox polymer can be positively charged, and there is a stronger electrostatic interaction between the redox polymer with a positive charge on the surface and the glucose enzyme with a negative charge on the surface, which is beneficial to improve the electron transfer efficiency.

[0131] In some examples, the redox polymer may include a hydrophilic group. In this case, the water solubility of the redox polymer as a whole can be improved, which is beneficial for coating processing (especially drop coating process). In some examples, the hydrophilic group can be any one of a quaternary ammonium group, a sulfonic acid group, and a carboxylic acid group.

[0132] In some examples, A 3 It can be a quaternary ammonium salt compound or a zwitterionic compound. In some examples, the quaternary ammonium salt compound can be any one of methacrylate quaternary ammonium salt, vinyl quaternary ammonium salt, alkyl trimethyl quaternary ammonium salt, hexadecyl trimethyl quaternary ammonium salt and dialkyl quaternary ammonium salt. In some examples, the zwitterionic compound can be any one of sulfonate betaine, carboxylate betaine and 2-methacryloyloxyethyl phosphorylcholine. In this case, the quaternary ammonium salt compound contains a quaternary ammonium group cation (i.e., a positively charged group and a hydrophilic group at the same time), and the zwitterionic compound also includes a positively charged group and a hydrophilic group at the same time. The quaternary ammonium salt compound or zwitterionic compound is used as A 3 Forming a part of the main chain can make the surface of the redox polymer positively charged, and at the same time can improve the water solubility of the entire redox polymer, which is convenient for drop coating processing.

[0133] In some examples, preferably, A 3 In this case, the redox polymer contains quaternary ammonium cations, which can improve the water solubility of the redox polymer as a whole and make the surface of the redox polymer positively charged.

[0134] In some examples, preferably, A 3 It may be a methacrylate quaternary ammonium salt. In this case, the water solubility of the redox polymer as a whole can be further improved.

[0135] In some examples, n 3 It can be any natural number between 100 and 1000. For example, n 3 It can be 100, 300, 500, 700, 900, or 1000. In some examples, n 1 and n 3 can be the same or different and be any natural number between 100 and 1000. In some examples, n 2 and n3 can be the same or different and be any natural number between 100 and 1000. In some examples, n 1 、n 2 and n 3 Can be the same or different.

[0136] In some examples, the monomer A in the main chain of the redox polymer (i.e., the chemical structure shown in formula (7)) can be regulated. 3 The total monomers in the main chain (A 1 , A 2 and A 3 ) percentage of the total number (the percentage is n 3 / (n 1 +n 2 +n 3 ) value), thereby changing the water solubility of the redox polymer. In this case, A 3 The larger the percentage, the more A in the main chain monomer of the redox polymer can be 3 The higher the content, the better the water solubility of the redox polymer. In some examples, monomer A 3 It can account for 5% to 50% of the main chain. 3 It can account for 5%, 15%, 25%, 35%, 45% or 50% of the backbone.

[0137] In some examples, preferably, the redox polymer has a structure as shown in the following formula (1):

[0138]

[0139] Among them, A 1 and A 2 The same and selected from any one of 4-vinylpyridine and N-vinylimidazole, A 3 is a quaternary ammonium salt compound or a zwitterionic compound, and X has a structure shown in the following formula (2):

[0140]

[0141] Where M is a transition metal, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 It is a nitrogen-containing heterocyclic ligand, and two of them combine to form three bidentate ligands; n 1 、n 2 and n 3 The same or different and any natural number between 100 and 1000.

[0142] In this case, A 3 The redox polymer is configured as a quaternary ammonium salt compound or a zwitterionic compound, and can include positively charged groups and hydrophilic groups. The positively charged groups can make the surface of the redox polymer positively charged, and can form a stronger electrostatic interaction with a substance with a negative charge on the surface during specific applications. The hydrophilic groups can improve the water solubility of the redox polymer as a whole, and are convenient for applying it in a solution processing process. In addition, since X includes 6 nitrogen-containing heterocyclic ligands and they are combined in pairs to form 3 bidentate ligands, the redox polymer can also have a lower redox equilibrium potential. When the redox polymer is used in a biosensor as an electron mediator, for example, when the redox polymer is used as an electron mediator in the sensing layer 110 of a glucose sensor, there is a stronger electrostatic interaction between the redox polymer with a positive charge on the surface and the glucose enzyme with a negative charge on the surface, which is beneficial to improving the efficiency of electron transfer. The redox polymer with good water solubility can facilitate the coating process (especially the drip coating process). The low potential of the redox polymer can also make the working potential required for the contact and reaction between glucose and the sensing layer 110 lower, thereby effectively reducing the redox reaction of high potential interferers and reducing the interference of high potential interferers on the electrical signal generated by the redox reaction of glucose molecules.

[0143] In some examples, preferably, A in the redox polymer 1 and A 2 The same and selected from any one of 4-vinylpyridine and N-vinylimidazole, A 3 It is a quaternary ammonium salt of methacrylate, and X has a structure shown in the following formula (2):

[0144]

[0145] Among them, M is osmium, L is 1 , L 2 , L 3 , L 4 , L 5 and L 6 is a nitrogen-containing heterocyclic ligand, and two of them are combined to form three bidentate ligands, and the three bidentate ligands include at least two imidazole-pyridine ligands; n 1 、n 2 and n 3 The same or different and any natural number between 100 and 1000.

[0146] In this case, the redox polymer contains quaternary ammonium cations, which can improve the water solubility of the polymer as a whole and make the surface of the polymer positively charged, which is beneficial to drip coating on the one hand, and can also make the polymer with positive charge on the surface and the glucose enzyme with negative charge on the surface have stronger electrostatic interaction, thereby improving the electron transfer efficiency; in addition, since X includes at least two imidazole-pyridine ligands, the redox polymer can have a lower redox equilibrium potential, so that the working potential required for glucose to contact and react with the sensing layer 110 on the working electrode 10 is lower, thereby effectively reducing the redox reaction of high potential interferents and reducing the interference of high potential interferents on the electrical signal generated by the redox reaction of glucose molecules.

[0147] In some examples, preferably, the structure of the redox polymer can be one of the following structures:

[0148]

[0149]

[0150]

[0151]

[0152]

[0153] In some examples, the probe 1 may include a semipermeable membrane. The semipermeable membrane may cover at least the sensing layer on the working electrode 10. In some examples, the semipermeable membrane may be a negatively charged membrane, and the negatively charged membrane may carry a negative charge. In this case, the negatively charged membrane can block some anionic interferents located outside the negatively charged membrane, thereby reducing the interference of the anionic interferents with the electrical signals generated by the redox reaction of the glucose molecules, thereby improving the anti-interference ability of the probe 1. In some examples, the anionic interferents may include ascorbic acid, uric acid, etc.

[0154] In some examples, a sensing layer of a low-potential redox polymer may be included on the semipermeable membrane and the working electrode 10. Thus, the anti-interference capability of the probe 1 against high-potential interferents and anionic interferents can be improved.

[0155] In some examples, the probe 1 may include a counter electrode. In some examples, the probe 1 may generate a current signal by performing an oxidation-reduction reaction between the glucose enzyme in the working electrode 10 and the glucose in the host body fluid and forming a loop with the counter electrode.

[0156] In some examples, the probe 1 may include a reference electrode. In some examples, the reference electrode may form a known and fixed potential difference with the body fluid. In this case, the potential difference between the working electrode 10 and the body fluid can be measured by the potential difference formed by the reference electrode and the working electrode 10, so as to accurately grasp the voltage generated by the working electrode 10. Thus, the electronic system 2 can automatically adjust and maintain the stability of the voltage at the working electrode 10 according to the pre-set voltage value to ensure that the measured current signal can accurately reflect the glucose concentration value.

[0157] In summary, in the first aspect of the present disclosure, a redox polymer having good water solubility and low redox equilibrium potential can be provided, and the monitoring probe 1 including the redox polymer has high sensitivity and strong anti-interference ability.

[0158] As described above, the second aspect of the present disclosure relates to a method for preparing a redox polymer. The redox polymer involved in the first aspect of the present disclosure can be prepared by the preparation method involved in the second aspect of the present disclosure.

[0159] In some examples, the preparation method may include the following steps: preparing a first polymer (step S100); grafting the metal complex X onto the first polymer to obtain a redox polymer (step S200). Thus, a redox polymer with good water solubility and low redox equilibrium potential can be prepared.

[0160] In the preparation method involved in the second aspect of the present disclosure, the redox polymer is consistent with the redox polymer of the first aspect of the present disclosure. For the redox polymer and the settings of the various components and parameters therein, please refer to the above description and will not be repeated here.

[0161] In some examples, in step S100, the first polymer may be a polymer containing a positively charged group and / or a hydrophilic group. In this case, the main chain of the subsequently synthesized redox polymer may also carry a positively charged group and / or a hydrophilic group. The positively charged group may make the surface of the redox polymer positively charged, and the redox polymer with a positive charge on the surface and the negatively charged glucose enzyme on the surface have a stronger electrostatic interaction, which is beneficial to improve the electron transfer efficiency; the hydrophilic group may improve the water solubility of the redox polymer as a whole, which is beneficial to the drop coating process.

[0162] In some examples, in step S100, the first polymer may be generated by reacting the nitrogen-containing heterocyclic compound and the first monomer. Specifically, the nitrogen-containing heterocyclic compound, the first monomer and the free radical initiator may be mixed and dissolved in an organic solvent to react and generate the first polymer.

[0163] In some examples, in step S100, the first polymer may have a chemical structure as shown in formula (7):

[0164]

[0165] Among them, A 1 and A 2 It can be a nitrogen-containing heterocyclic compound, A 3 It can be the first monomer.

[0166] The formula (7) involved in the second aspect of the present disclosure is consistent with the content disclosed in the formula (7) involved in the first aspect of the present disclosure, and will not be repeated here.

[0167] In some examples, in step S100, the free radical initiator can be selected from any one of ammonium persulfate, hydrogen peroxide, benzoyl peroxide, tert-butyl ketone peroxide, 2,2'-diisopropyl di(phenyl)peroxide (AIBN) or ferric chloride, thereby initiating and promoting the chemical reaction.

[0168] In some examples, in step S100, the organic solvent may be selected from any one of toluene, dimethyl sulfoxide (DMSO), acetone, chloroform, acetonitrile or N,N-dimethylformamide (DMF), thereby promoting the dissolution of reactants in the chemical reaction and the progress of the chemical reaction.

[0169] In some examples, in step S100, the first monomer may be a quaternary ammonium salt compound or a zwitterionic compound. In this case, a first polymer containing a hydrophilic group can be synthesized, thereby increasing the water solubility of the first polymer as a whole and making the surface of the first polymer positively charged.

[0170] In some examples, in step S100, the quaternary ammonium salt compound can be any one of methacrylate quaternary ammonium salt, alkyl trimethyl quaternary ammonium salt, hexadecyl trimethyl quaternary ammonium salt and dialkyl quaternary ammonium salt. Thus, a first polymer containing quaternary ammonium cations can be synthesized, so that the surface of the first polymer is positively charged, and the water solubility of the first polymer as a whole can be improved.

[0171] In some examples, in step S100, the zwitterionic compound may be any one of sulfonate betaine, carboxylate betaine and 2-methacryloyloxyethyl phosphorylcholine. Thus, a first polymer containing a hydrophilic group can be synthesized. In some examples, the hydrophilic group may be any one of a quaternary ammonium group, a sulfonic acid group and a carboxylic acid group.

[0172] In some examples, in step S100, the nitrogen-containing heterocyclic compound can be selected from any one of pyridine derivatives and imidazole derivatives. In some examples, in step S100, the nitrogen-containing heterocyclic compound can be selected from any one of 4-vinylpyridine, 2-vinylpyridine and N-vinylimidazole.

[0173] In some examples, in step S200 , the metal complex X may be grafted to the first polymer to obtain a redox polymer.

[0174] In some examples, in step S200, the redox polymer may have a structure as shown in formula (1):

[0175]

[0176] The formula (1) involved in the second aspect of the present disclosure is consistent with the content disclosed in the formula (1) involved in the first aspect of the present disclosure, and will not be repeated here.

[0177] In some examples, the step of grafting the metal complex X to the first polymer may include: selecting a metal complex X with a free amino group (step S21); modifying the first polymer so that the first polymer forms a side chain including a carboxyl group (step S22); and covalently bonding the first polymer and the metal complex X via an amide bond by dehydration condensation (step S23). In this case, the connection stability between the metal complex X and the first polymer can be improved by dehydration condensation. The order of step S21 and step S22 is not specific, and step S21 can be performed first, or step S22 can be performed first, or step S21 and step S22 can be performed simultaneously.

[0178] In some examples, in step S200, the connection between the first polymer and X has a structure shown in formula (6):

[0179]

[0180] The formula (6) involved in the second aspect of the present disclosure is consistent with the content disclosed in the formula (6) involved in the first aspect of the present disclosure. For details, please refer to the description of formula (6) in the first aspect of the present disclosure, which will not be repeated here.

[0181] In some examples, in step S200, the first polymer and the halogenated fatty acid compound can be mixed and dissolved in an organic solvent, the reaction system can be heated to react to generate a first polymer with a carboxyl group on the side chain, and then the metal complex X and the first polymer with a carboxyl group on the side chain can be dissolved in an organic solvent containing an activator and a catalyst to generate a redox polymer.

[0182] In some examples, in step S200, the halogenated fatty acid compound can be selected from any one of 6-bromohexanoic acid, 6-chlorohexanoic acid or 6-chloroheptanoic acid. In this case, the first polymer is modified by the halogenated fatty acid compound, so that the first polymer can form a side chain including a carboxyl group.

[0183] In some examples, in step S200, the organic solvent may be selected from any one of toluene, dimethyl sulfoxide (DMSO), acetone, chloroform, or N-dimethylformamide (DMF), thereby promoting the dissolution of reactants in the chemical reaction and the progress of the chemical reaction.

[0184] In some examples, in step S200, the activator can be selected from any one of 1-[(dimethylamino)methyl]-1H-1,2,3-triazolo(4,5-b)pyridine-3-oxide hexafluorophosphate (HATU), O-(6-chloro-1-hydroxybenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HCTU), 2-succinimidyl-1,1,3,3-tetramethyluronium tetrafluoroborate (TSTU) or O-benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU).

[0185] In some examples, in step S200 , the catalyst may be selected from any one of triethylenediamine (DIBCO), diisopropylethylamine (DIPEA), or triethylamine (TEA).

[0186] In some examples, in step S200, the metal complex X may have a structure as shown in the following formula (2):

[0187] The formula (2) involved in the second aspect of the present disclosure is consistent with the content disclosed in the formula (2) involved in the first aspect of the present disclosure, and will not be repeated here.

[0188] In some examples, in step S200, M may be a transition metal. In some examples, in step S200, M may be osmium. In some examples, in step S200, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 They can combine in pairs to form bidentate ligands.

[0189] In some examples, two imidazole-pyridine ligands may be included in the three bidentate ligands of X. In this case, the redox polymer can have a lower redox equilibrium potential, so that the working potential required for glucose to contact and react with the sensing layer 110 on the working electrode 10 is lower, thereby effectively reducing the redox reaction of high-potential interferents and reducing the interference of high-potential interferents on the electrical signal generated by the redox reaction of glucose molecules.

[0190] In some examples, in step S200, L 1 , L 2 , L 3 , L 4 , L 5 and L 6 It can be selected from any one of pyridine and imidazole.

[0191] In some examples, in step S200, the metal complex X may have a structure as shown in the following formula (3):

[0192]

[0193] The formula (3) involved in the second aspect of the present disclosure is consistent with the content disclosed in the formula (3) involved in the first aspect of the present disclosure, and will not be repeated here.

[0194] In some examples, in step S200, after the metal complex X is grafted onto the first polymer, the crude product generated by the reaction can be further refined by a chloride ion exchange resin, thereby obtaining a purified redox polymer.

[0195] In some examples, a redox polymer can be prepared by steps S100 to S200 as described above. Hereinafter, an example of a synthesis method of a redox polymer is described. It should be noted that the following chemical expression is only a schematic representation of the reaction process, and does not mean that the following chemical expression is a limitation of the preparation steps S100 to S200 of the present disclosure.

[0196] The following is an example of chemical expressions of chemical reactions involved in step S100 to step S200:

[0197]

[0198] In step S100, 4-vinylpyridine and a quaternary ammonium salt compound may be mixed and dissolved in a DMSO solvent, and an AIBN reagent may be added to the solution as an initiator of a chemical reaction, and the reaction system may be reacted at 80° C. for 3 hours to generate a first polymer;

[0199] In step S200, the first polymer and 6-bromohexanoic acid can be mixed and dissolved in a DMF solvent, the reaction system can be heated, and the temperature of the reaction system can be maintained at 90° C., and a first polymer with a carboxyl group on the side chain can be generated after the reaction; the first polymer with a carboxyl group on the side chain can be dissolved in a DMF solvent, TEA reagent and HATU reagent can be added to the reaction system, and after the reaction system is stirred at room temperature for 6 hours, a metal complex X containing a free amino group is added to the reaction system, and the reaction is continued for 24 hours, and the metal complex X and the first polymer with a carboxyl group on the side chain undergo a dehydration condensation reaction to generate an amide bond; and a redox polymer can be obtained.

[0200] The second aspect of the present disclosure may also include a method for preparing a glucose monitoring probe 1, which can prepare a glucose monitoring probe 1 including the redox polymer involved in the first aspect of the present disclosure.

[0201] Figure 5 is a flow chart showing a method for preparing the glucose monitoring probe 1 according to an example of the present disclosure.

[0202] In some examples, the preparation method of the glucose monitoring probe 1 may include the following steps in addition to the above steps S100 and S200: preparing a sensing layer solution including a redox polymer (step S300); dripping the sensing layer solution onto the surface of the working electrode 10 to form a sensing layer 110, and obtaining the glucose monitoring probe 1 (step S400). Thus, the glucose monitoring probe 1 including the redox polymer can be prepared.

[0203] In some examples, as described above, in step S300, a sensing layer solution including a redox polymer may be prepared. That is, in step S300, the sensing layer solution may include a redox polymer.

[0204] In some examples, in step S300, the sensing layer solution may include glucose enzyme, wherein the glucose enzyme may be glucose oxidase or glucose dehydrogenase.

[0205] In some examples, in step S300, the sensing layer solution may include a crosslinker. Wherein, the crosslinker may be selected from any one of glutaraldehyde, polyethylene glycol diglycidyl ether (PEGDGE) and genipin. In some examples, in step S300, the sensing layer solution may include a redox polymer, a glucase and a crosslinker. In this case, the crosslinker is capable of connecting the glucase to the redox polymer. In some examples, the mass fraction of the crosslinker may be 5% to 15%. For example, the mass fraction of the crosslinker may be 5%, 8%, 10%, 12% or 15%. In some examples, the mass ratio of the redox polymer and the glucase may be 2:8 to 8:2. For example, the mass ratio of the redox polymer and the glucase may be 2:8, 3:7, 4:6, 5:5, 6:4, 7:3 or 8:2.

[0206] In some examples, in step S400, the sensing layer solution can be applied to the surface of the working electrode 10 to form the sensing layer 110, thereby obtaining the glucose monitoring probe 1. For example, the sensing layer solution can be applied to the surface of the working electrode 10 by drop coating, spin coating, dip pulling, drop coating, or spray coating. In some examples, in step S400, preferably, the sensing layer solution can be applied to the surface of the working electrode 10 by drop coating.

[0207] In some examples, in step S400, the sensing layer solution may be drop-coated on the working electrode 10 in the form of a plurality of discrete points to form the sensing layer 110. In some examples, in step S400, a plurality of discrete points may constitute the sensing layer 110. In some examples, in step S400, a plurality of points with overlapping edges may also be drop-coated on the working electrode 10 to form a sensing layer 110 in which a plurality of points are connected in a line. In this case, it is convenient to set more sensing layer solutions on the working electrode 10, which can be beneficial to improve the sensitivity of the working electrode 10.

[0208] In summary, in the second aspect of the present disclosure, by using the preparation method to prepare a redox polymer, a redox polymer having good water solubility and a low redox equilibrium potential can be obtained.

[0209] The third aspect of the present disclosure provides a biosensor. The biosensor involved in the third aspect of the present disclosure includes the redox polymer involved in the first aspect of the present disclosure. The redox polymer and the settings of the components and parameters therein can be found in the above description, which will not be repeated here. The synthesis method of the redox polymer in the biosensor involved in the third aspect of the present disclosure is consistent with the content disclosed in the preparation method involved in the second aspect of the present disclosure, which will not be repeated here.

[0210] In some examples, the biosensor may include a working electrode. The working electrode may be provided with a sensitive substance corresponding to the target analyte and the redox polymer involved in the first aspect of the present disclosure. Thus, the target analyte can be sensed by the biosensor, and the biosensor can be made to have anti-interference ability against high-potential interferents.

[0211] The third aspect of the present disclosure relates to a biosensor having high sensitivity and strong anti-interference ability, wherein the biosensor includes a redox polymer having a low redox potential. In this case, the biosensor can play an anti-interference role against high-potential interferents in the subject's body.

[0212] The redox polymer provided by the present disclosure is described in detail below in conjunction with the examples and comparative examples, but they should not be construed as limiting the scope of protection of the present disclosure. In order to verify the anti-interference effect of the redox polymer involved in the present disclosure on high-potential interferers, uric acid (potential of about 400mV) and acetaminophen (potential of about 480mV) were used as interferers and added to the examples for experiments.

[0213] First, a plurality of glucose monitoring probes 1 with working electrodes 10 of the same specifications are prepared for use.

[0214] [Example]

[0215] Example 1

[0216] 1. Mix and dissolve 4-vinylpyridine, a quaternary ammonium salt compound and an AIBN reagent in a molar ratio of 90:9:1 in a DMSO solvent to react and generate a first polymer.

[0217] 2. Mix and dissolve the first polymer and 6-bromohexanoic acid in a molar ratio of 4:1 in a DMF solvent, heat the reaction system, and maintain the temperature of the reaction system at 90° C. to react and generate a first polymer with a carboxyl group on the side chain.

[0218] 3. The metal complex X containing free amino groups and the first polymer with carboxyl groups on the side chains are dissolved in a DMF solvent containing HATU reagent and TEA reagent at a molar ratio of 5:1, wherein the molar ratio of HATU to the first polymer with carboxyl groups on the side chains is 0.2, and the molar ratio of TEA to the first polymer with carboxyl groups on the side chains is 0.4. The metal complex X and the first polymer with carboxyl groups on the side chains undergo a dehydration condensation reaction to generate a redox polymer. The redox polymer has a structure shown in the following formula (8):

[0219]

[0220] 4. The redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode, and after drying, a sensing layer was formed, thereby obtaining the glucose monitoring probe (referred to as the probe) of Example 1. The dissolution time of the redox polymer of Example 1 was less than 0.5 hours, and the sensing layer solution after uniform mixing was clear and transparent. The viscosity of the sensing layer solution after uniform mixing was 1.33 cp (centipoise), and the redox polymer of Example 1 had good water solubility.

[0221] The glucose monitoring probe of Example 1 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Figure 6 2 is a cyclic voltammetry graph showing the probe of Example 1 after 200 cycles. Figure 7 FIG. 1 is a graph showing the oxidation peak current-cycle number curve of Example 1. Figure 8 3 is a graph showing the oxidation peak current-storage days curve of the probe of Example 1. Fig. 9 3 is a graph showing the sensitivity response of the probe of Example 1 versus glucose concentration.

[0222] from Figure 6 It can be seen from the figure that as the number of cycles changes, the position, height and width of the oxidation peak of the redox polymer in Example 1 remain roughly unchanged, and the redox polymer in Example 1 has good stability. Figure 6 The oxidation peak E of the redox polymer in Example 1 can be read from ox =19mV, restore peak value E red =-67mV, redox equilibrium potential E 1 / 2 =-24 mV. Compared with the high potential interferents, the redox polymer in Example 1 has a lower redox equilibrium potential.

[0223] from Figure 7 It can be seen that the attenuation rate of the oxidation peak current value of the probe in Example 1 in the phosphate (PBS) buffer solution is 5.5%. It can be seen that with the change of the number of cycles, the oxidation peak current value of Example 1 has a slight downward trend, but remains stable overall.

[0224] from Figure 8 It can be seen that the probe of Example 1 is stored in the PBS buffer solution for 30 days, and the average daily attenuation rate of the oxidation peak current value is 0.19%. It can be seen that with the increase in the number of storage days, the oxidation peak current value of Example 1 changes slightly, but generally tends to be stable.

[0225] The sensitivity test results of the probe in Example 1 under different glucose concentrations were linearly fitted, and the fitting equation obtained was y=1.2786x+0.8465, as shown in FIG. Fig. 9 As shown, the R of the fitting equation 2 >0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of Example 1 is 1.2786, indicating that the sensitivity of the probe of Example 1 is higher.

[0226] Example 2

[0227] 1. Mix and dissolve 4-vinylpyridine, a quaternary ammonium salt compound and an AIBN reagent in a molar ratio of 90:9:1 in a DMSO solvent to react and generate a first polymer.

[0228] 2. Mix and dissolve the first polymer and 6-bromohexanoic acid in a molar ratio of 4:1 in a DMF solvent, heat the reaction system, and maintain the temperature of the reaction system at 90° C. to react and generate a first polymer with a carboxyl group on the side chain.

[0229] 3. The metal complex X containing free amino groups and the first polymer with carboxyl groups on the side chains are dissolved in a DMF solvent containing HATU reagent and TEA reagent at a molar ratio of 5:1, wherein the molar ratio of HATU to the first polymer with carboxyl groups on the side chains is 0.2, and the molar ratio of TEA to the first polymer with carboxyl groups on the side chains is 0.4. The metal complex X and the first polymer with carboxyl groups on the side chains undergo a dehydration condensation reaction to generate a redox polymer. The redox polymer has a structure shown in the following formula (9):

[0230]

[0231] 4. The redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode, and dried to form a sensing layer, thereby obtaining the glucose monitoring probe of Example 2. The dissolution time of the redox polymer of Example 2 was less than 0.5 hours, and the sensing layer solution after mixing uniformly was clear and transparent. The viscosity of the sensing layer solution after mixing uniformly was 1.36 cp (centipoise), and the redox polymer of Example 2 had good water solubility.

[0232] The glucose monitoring probe of Example 2 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig.10 2 is a cyclic voltammetry graph showing the probe of Example 2 after 200 cycles. Fig.11 2 is a graph showing the oxidation peak current-cycle number curve of Example 2. Fig.123 is a graph showing the oxidation peak current-storage days curve of the probe of Example 2. Fig.13 3 is a graph showing the sensitivity response of the probe of Example 2 versus glucose concentration.

[0233] from Fig.10 It can be seen from the figure that as the number of cycles changes, the position, height and width of the oxidation peak of the redox polymer in Example 2 remain roughly unchanged, and the redox polymer in Example 2 has good stability. Fig.10 The oxidation peak E of the redox polymer in Example 2 can be read from ox =160mV, restore peak value E red =40mV, redox equilibrium potential E 1 / 2 =100 mV. Compared with the high potential interferent, the redox polymer in Example 2 has a lower redox equilibrium potential.

[0234] from Fig.11 It can be seen that the attenuation rate of the oxidation peak current value of the probe of Example 2 in the PBS buffer solution is 4.3%. It can be seen that with the change of the number of cycles, the oxidation peak current value of Example 2 has a slight downward trend, but remains stable overall.

[0235] from Fig.12 It can be seen that the probe of Example 2 is stored in the PBS buffer solution for 30 days, and the average daily attenuation rate of the oxidation peak current value is 0.42%. It can be seen that with the increase in the number of storage days, the oxidation peak current value of Example 2 changes slightly, but generally tends to be stable.

[0236] The sensitivity test results of the probe in Example 2 under different glucose concentrations were linearly fitted, and the fitting equation obtained was y=1.2003x+0.5496. Fig.13 As shown, the R of the fitting equation 2 >0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of Example 2 is 1.2003, indicating that the sensitivity of the probe of Example 2 is higher.

[0237] Example 3

[0238] 1. Mix and dissolve 4-vinylpyridine, a zwitterionic compound and an AIBN reagent in a molar ratio of 90:9:1 in a DMSO solvent to react and generate a first polymer.

[0239] 2. Mix and dissolve the first polymer and 6-bromohexanoic acid in a molar ratio of 4:1 in a DMF solvent, heat the reaction system, and maintain the temperature of the reaction system at 90° C. to react and generate a first polymer with a carboxyl group on the side chain.

[0240] 3. The metal complex X containing free amino groups and the first polymer with carboxyl groups on the side chains are dissolved in a DMF solvent containing HATU reagent and TEA reagent at a molar ratio of 5:1, wherein the molar ratio of HATU to the first polymer with carboxyl groups on the side chains is 0.2, and the molar ratio of TEA to the first polymer with carboxyl groups on the side chains is 0.4. The metal complex X and the first polymer with carboxyl groups on the side chains undergo a dehydration condensation reaction to generate a redox polymer. The redox polymer has a structure shown in the following formula (10):

[0241]

[0242] 4. The redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode and dried to form a sensing layer, thereby obtaining the glucose monitoring probe of Example 3. The dissolution time of the redox polymer of Example 3 was less than 0.5 hours, and the sensing layer solution after mixing uniformly was clear and transparent. The viscosity of the sensing layer solution after mixing uniformly was 1.45 cp (centipoise), and the redox polymer of Example 3 had good water solubility.

[0243] The glucose monitoring probe of Example 3 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig.14 is a graph showing a cyclic voltammetry curve of the probe of Example 3. Fig.15 3 is a graph showing the sensitivity response of the probe of Example 3 versus glucose concentration.

[0244] from Fig.14 It can be seen from the figure that as the number of cycles changes, the position, height and width of the oxidation peak of the redox polymer in Example 3 remain roughly unchanged, and the redox polymer in Example 3 has good stability. Fig.14 The oxidation peak E of the redox polymer in Example 3 can be read from ox =22mV, restore peak value E red =-35mV, redox equilibrium potential E 1 / 2 =-6 mV. Compared with the high potential interferents, the redox polymer in Example 3 has a lower redox equilibrium potential.

[0245] The sensitivity test results of the probe in Example 3 under different glucose concentrations were linearly fitted, and the obtained fitting equation was y=1.1072x-0.1548, as shown in FIG. Fig.15 As shown, the R of the fitting equation 2>0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of Example 3 is 1.1072, indicating that the sensitivity of the probe of Example 3 is higher.

[0246] Example 4

[0247] 1. Mix and dissolve 4-vinylpyridine, a zwitterionic compound and an AIBN reagent in a molar ratio of 90:9:1 in a DMSO solvent to react and generate a first polymer.

[0248] 2. Mix and dissolve the first polymer and 6-bromohexanoic acid in a molar ratio of 4:1 in a DMF solvent, heat the reaction system, and maintain the temperature of the reaction system at 90° C. to react and generate a first polymer with a carboxyl group on the side chain.

[0249] 3. The metal complex X containing free amino groups and the first polymer with carboxyl groups on the side chains are dissolved in a DMF solvent containing HATU reagent and TEA reagent at a molar ratio of 5:1, wherein the molar ratio of HATU to the first polymer with carboxyl groups on the side chains is 0.2, and the molar ratio of TEA to the first polymer with carboxyl groups on the side chains is 0.4. The metal complex X and the first polymer with carboxyl groups on the side chains undergo a dehydration condensation reaction to generate a redox polymer. The redox polymer has a structure shown in the following formula (11):

[0250]

[0251] 4. The redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode and dried to form a sensing layer, thereby obtaining the glucose monitoring probe of Example 4. The dissolution time of the redox polymer of Example 4 was less than 0.5 hours, and the sensing layer solution after mixing uniformly was clear and transparent. The viscosity of the sensing layer solution after mixing uniformly was 1.49 cp (centipoise), and the redox polymer of Example 4 had good water solubility.

[0252] The glucose monitoring probe of Example 4 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig.16 is a graph showing a cyclic voltammetry curve of the probe of Example 4. Fig.17 3 is a graph showing the sensitivity response of the probe of Example 4 versus glucose concentration.

[0253] from Fig.16 It can be seen from the figure that as the number of cycles changes, the position, height and width of the oxidation peak of the redox polymer in Example 4 remain roughly unchanged, and the redox polymer in Example 4 has good stability. Fig.16 The oxidation peak E of the redox polymer in Example 4 can be read from ox =22mV, restore peak value E red =-42mV, redox equilibrium potential E 1 / 2 =-10 mV. Compared with the high potential interferent, the redox polymer in Example 4 has a lower redox equilibrium potential.

[0254] The sensitivity test results of the probe in Example 4 under different glucose concentrations were linearly fitted, and the obtained fitting equation was y=1.0632x-0.0775, as shown in FIG. Fig.17 As shown, the R of the fitting equation 2 >0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of Example 4 is 1.0632, indicating that the sensitivity of the probe of Example 4 is higher.

[0255] [Comparative Example]

[0256] Comparative Example 1

[0257] Compared with Example 1, only the redox polymer in the probe is replaced from the redox polymer in Example 1 to a redox polymer having a structure shown in the following formula (12):

[0258]

[0259] A redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode and dried to form a sensing layer, thereby obtaining a glucose monitoring probe of Comparative Example 1. The dissolution time of the redox polymer of Comparative Example 1 was 24 hours, and the viscosity of the sensing layer solution after uniform mixing was 3.55 cp (centipoise). The water solubility of the redox polymer of Comparative Example 1 was poorer than that of the redox polymer in the embodiment.

[0260] The glucose monitoring probe of Comparative Example 1 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig.18 is a graph showing a cyclic voltammetry curve of the probe of Comparative Example 1. Fig.19 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 1.

[0261] from Fig.18 It can be seen that the oxidation peak E of the redox polymer in Comparative Example 1 ox =210mV, restore peak value E red =116mV, redox equilibrium potential E1 / 2 =163 mV. Compared with the examples, the redox polymer in Comparative Example 1 has a higher redox equilibrium potential.

[0262] The sensitivity test results of the probe of Comparative Example 1 under different glucose concentrations were linearly fitted, and the fitting equation obtained was y=0.4078x+0.0198, as shown in FIG. Fig.19 As shown, the R of the fitting equation 2 >0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of comparative example 1 is 0.4078, indicating that the sensitivity of the probe of comparative example 1 is lower than that of the probe of the embodiment.

[0263] Comparative Example 2

[0264] Compared with Example 1, only the redox polymer in the probe is replaced from the redox polymer in Example 1 to a redox polymer having a structure shown in the following formula (13):

[0265]

[0266] A redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode and dried to form a sensing layer, thereby obtaining a glucose monitoring probe of Comparative Example 2. The dissolution time of the redox polymer of Comparative Example 2 was 24 hours, and the viscosity of the sensing layer solution after uniform mixing was 8.25 cp (centipoise). The water solubility of the redox polymer of Comparative Example 2 was poorer than that of the redox polymer in the embodiment.

[0267] The glucose monitoring probe of Comparative Example 2 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig. 20 is a graph showing a cyclic voltammetry curve of the probe of Comparative Example 2. Fig.21 3 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 2.

[0268] from Fig. 20 It can be seen that the oxidation peak E of the redox polymer in Comparative Example 2 ox =250mV, restore peak value E red =115mV, redox equilibrium potential E 1 / 2 =183 mV. Compared with the examples, the redox polymer in Comparative Example 2 has a higher redox equilibrium potential.

[0269] The sensitivity test results of the probe of Comparative Example 2 under different glucose concentrations were linearly fitted, and the fitting equation obtained was y=0.1965x+0.3203, as shown in FIG. Fig.21 As shown, the R of the fitting equation 2 >0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of Comparative Example 2 is 0.1965, indicating that the sensitivity of the probe of Comparative Example 2 is lower than that of the probe of the embodiment.

[0270] Comparative Example 3

[0271] Compared with Example 1, only the redox polymer in the probe is replaced from the redox polymer in Example 1 to a redox polymer having a structure shown in the following formula (14):

[0272]

[0273] A redox polymer, glucose oxidase and PEGDGE reagent in a mass ratio of 6:3:1 were mixed uniformly to prepare a sensing layer solution, and the sensing layer solution was drop-coated on the surface of the working electrode and dried to form a sensing layer, thereby obtaining a glucose monitoring probe of Comparative Example 3. The dissolution time of the redox polymer of Comparative Example 3 was 24 hours, and the viscosity of the sensing layer solution after uniform mixing was 9.58 cp (centipoise). The water solubility of the redox polymer of Comparative Example 3 was poorer than that of the redox polymer in the embodiment.

[0274] The glucose monitoring probe of Comparative Example 3 was tested using cyclic voltammetry at a cycle rate of 50 mV / s. Fig. 22 is a cyclic voltammetry graph showing the probe of Comparative Example 3. Fig.23 3 is a graph showing the sensitivity response-glucose concentration curve of the probe of Comparative Example 3.

[0275] from Fig. 22 It can be seen that the oxidation peak E ox =225mV, restore peak value E red =158mV, redox equilibrium potential E 1 / 2 =192 mV. Compared with the examples, the redox polymer in Comparative Example 3 has a higher redox equilibrium potential.

[0276] The sensitivity test results of the probe of Comparative Example 3 under different glucose concentrations were linearly fitted, and the fitting equation obtained was y=0.1681x+0.2542, as shown in Fig.23 As shown, the R of the fitting equation 2>0.99, it can be seen that the sensitivity is linearly correlated with the glucose concentration. The larger the slope of the fitting equation, the higher the sensitivity of the probe. The slope of the fitting equation of comparative example 3 is 0.1681, indicating that the sensitivity of the probe of comparative example 3 is lower than that of the probe of the embodiment.

[0277] The anti-interference ability of the probes of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 for uric acid and acetaminophen was tested, as follows:

[0278] 1. The probe of Example 1 was immersed in PBS buffer solutions containing glucose concentrations of 5 mmol / L (millimoles per liter) and 15 mmol / L, and the measured current value was recorded as reading 1. The results are shown in Table 1.

[0279] 2. The probe of Example 1 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and uric acid concentration of 23.5 mg / dL (milligrams per deciliter), and the measured current value was recorded as reading 2. The results are shown in Table 1.

[0280] 3. The probe of Example 1 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and acetaminophen concentration of 20 mg / dL, and the measured current value was recorded as reading 3. The results are shown in Table 1.

[0281] 4. The probe of Example 2 was immersed in PBS buffer solutions containing glucose concentrations of 5 mmol / L (millimoles per liter) and 15 mmol / L, and the measured current value was recorded as reading 4. The results are shown in Table 2.

[0282] 5. The probe of Example 2 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and uric acid concentration of 23.5 mg / dL (milligrams per deciliter), and the measured current value was recorded as reading 5. The results are shown in Table 2.

[0283] 6. The probe of Example 2 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and acetaminophen concentration of 20 mg / dL, and the measured current value was recorded as reading 6. The results are shown in Table 2.

[0284] 7. The probe of Comparative Example 1 was immersed in PBS buffer solutions containing glucose concentrations of 5 mmol / L and 15 mmol / L, and the measured current value was recorded as reading 7. The results are shown in Table 3.

[0285] 8. The probe of comparative example 1 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and uric acid concentration of 23.5 mg / dL, and the measured current value was recorded as reading 8. The results are shown in Table 3.

[0286] 9. The probe of comparative example 1 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and acetaminophen concentration of 20 mg / dL, and the measured current value was recorded as reading 9. The results are shown in Table 3.

[0287] 10. The probe of Comparative Example 2 was immersed in PBS buffer solutions containing glucose concentrations of 5 mmol / L and 15 mmol / L, and the measured current value was recorded as reading 10. The results are shown in Table 4.

[0288] 11. The probe of comparative example 2 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and uric acid concentration of 23.5 mg / dL, and the measured current value was recorded as reading 11. The results are shown in Table 4.

[0289] 12. The probe of Comparative Example 2 was immersed in a PBS buffer solution containing glucose concentrations of 5 mmol / L and 15 mmol / L and acetaminophen concentration of 20 mg / dL, and the measured current value was recorded as reading 12. The results are shown in Table 4.

[0290] Table 1 below shows the experimental data of the test of the anti-interference ability of the probe of Example 1 for uric acid and acetaminophen:

[0291] Table 1

[0292]

[0293] In Table 1, the current change rate 1 is expressed as the change rate of reading 2 relative to reading 1, and its calculation formula is current change rate 1 = (reading 2-reading 1) / reading 1*100%, which can show the anti-interference ability of the probe of Example 1 to uric acid; the current change rate 2 is expressed as the change rate of reading 3 relative to reading 1, and its calculation formula is current change rate 2 = (reading 3-reading 1) / reading 1*100%, which can show the anti-interference ability of the probe of Example 1 to acetaminophen. The larger the absolute value of the current change rate, the weaker the anti-interference ability of the probe.

[0294] It can be seen from Table 1 that when the probe of Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 0.27%; when the probe of Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 0.05%.

[0295] It can be seen from Table 1 that when the probe of Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is -0.68%; when the probe of Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is -0.36%.

[0296] Table 2 below shows the experimental data of the test of the anti-interference ability of the probe of Example 2 for uric acid and acetaminophen:

[0297] Table 2

[0298]

[0299] In Table 2, the current change rate 3 is expressed as the change rate of reading 5 relative to reading 4, and its calculation formula is current change rate 3 = (reading 5-reading 4) / reading 4*100%, which can show the anti-interference ability of the probe of Example 2 to uric acid; the current change rate 4 is expressed as the change rate of reading 6 relative to reading 4, and its calculation formula is current change rate 4 = (reading 6-reading 4) / reading 4*100%, which can show the anti-interference ability of the probe of Example 2 to acetaminophen. The larger the absolute value of the current change rate, the weaker the anti-interference ability of the probe.

[0300] It can be seen from Table 2 that when the probe of Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 4.20%; when the probe of Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 2.56%.

[0301] It can be seen from Table 2 that when the probe of Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 10.73%; when the probe of Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 4.62%.

[0302] Table 3 below shows the experimental data of the test of the anti-interference ability of the probe of Comparative Example 1 for uric acid and acetaminophen:

[0303] Table 3

[0304]

[0305] In Table 3, the current change rate 5 is expressed as the change rate of reading 8 relative to reading 7, and its calculation formula is current change rate 5 = (reading 8-reading 7) / reading 7*100%, which can show the anti-interference ability of the probe of Comparative Example 1 to uric acid; the current change rate 6 is expressed as the change rate of reading 9 relative to reading 7, and its calculation formula is current change rate 6 = (reading 9-reading 7) / reading 7*100%, which can show the anti-interference ability of the probe of Comparative Example 1 to acetaminophen. The larger the absolute value of the current change rate, the weaker the anti-interference ability of the probe.

[0306] It can be seen from Table 3 that when the probe of Comparative Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 12.08%; when the probe of Comparative Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 6.97%.

[0307] It can be seen from Table 3 that when the probe of Comparative Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 52.17%; when the probe of Comparative Example 1 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 19.73%.

[0308] Table 4 below shows the experimental data of the test of the anti-interference ability of the probe of Comparative Example 2 for uric acid and acetaminophen:

[0309] Table 4

[0310]

[0311] In Table 4, the current change rate 7 is expressed as the change rate of reading 11 relative to reading 10, and its calculation formula is current change rate 7 = (reading 11-reading 10) / reading 10*100%, which can show the anti-interference ability of the probe of Comparative Example 2 to uric acid; the current change rate 8 is expressed as the change rate of reading 12 relative to reading 10, and its calculation formula is current change rate 8 = (reading 12-reading 10) / reading 10*100%, which can show the anti-interference ability of the probe of Comparative Example 2 to acetaminophen. The larger the absolute value of the current change rate, the weaker the anti-interference ability of the probe.

[0312] It can be seen from Table 4 that when the probe of Comparative Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 12.31%; when the probe of Comparative Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and a uric acid concentration of 23.5 mg / dL, the current change rate is 6.10%.

[0313] It can be seen from Table 4 that when the probe of Comparative Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 5 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 75.38%; when the probe of Comparative Example 2 is immersed in a PBS buffer solution containing a glucose concentration of 15 mmol / L and an acetaminophen concentration of 20 mg / dL, the current change rate is 31.71%.

[0314] Therefore, it can be seen that when the probes of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are in the same solution system, the absolute value of the current change rate of the probes of Comparative Example 1 and Comparative Example 2 is greater than the absolute value of the current change rate of the probes of Example 1 and Example 2. In other words, the anti-interference ability of the probes of Example 1 and Example 2 to uric acid and acetaminophen is better than the anti-interference ability of the probes of Comparative Example 1 and Comparative Example 2 to uric acid and acetaminophen. The reason is that the redox polymer with lower redox equilibrium potential can reduce the redox reaction of high potential interfering substances (uric acid and acetaminophen, etc.), and then can reduce the interference of the electrical signal produced by the redox reaction of glucose molecules by high potential interfering substances (uric acid and acetaminophen, etc.).

[0315] In summary, the sensitivity of the probes of Examples 1 to 4 is linearly correlated with the glucose concentration, indicating that the probes provided by the present disclosure have good sensitivity. In addition, the working potential required for the probes of Examples 1 to 4 is relatively low, and glucose can be brought into contact with the sensing layer on the working electrode to react between -100mV and 100mV, which can reduce the interference of high-potential interferents with the electrical signals generated by the redox reaction of glucose molecules. Thus, the present disclosure can provide a redox polymer with good water solubility and low redox equilibrium potential.

[0316] Although the present disclosure is specifically described above in conjunction with the accompanying drawings and examples, it is to be understood that the above description does not limit the present disclosure in any form. Those skilled in the art may modify and change the present disclosure as needed without departing from the essential spirit and scope of the present disclosure, and these modifications and changes all fall within the scope of the present disclosure.

Claims

1. A redox polymer, characterized in that The redox polymer has a structure as shown in the following formula (1): in, A1 and A2 are the same and are selected from any one of 4-vinylpyridine and N-vinylimidazole, A3 is a quaternary ammonium salt compound or a zwitterionic compound, X has the structure shown in the following formula (2): in, M is a transition metal, L1, L2, L3, L4, L5 and L6 are nitrogen-containing heterocyclic ligands, and they are combined in pairs to form three bidentate ligands; n1, n2 and n3 are the same or different and are any natural number between 100 and 1000.

2. The redox polymer according to claim 1, characterized in that Among the three bidentate ligands of X, at least two are imidazole-pyridine ligands.

3. The redox polymer according to claim 1, characterized in that M is osmium.

4. The redox polymer according to claim 1, characterized in that The zwitterionic compound is any one of sulfonate betaine, carboxylate betaine and 2-methacryloyloxyethyl phosphorylcholine.

5. The redox polymer according to claim 1, characterized in that X has the structure shown in the following formula (3): Wherein, Y is a halogen ion, and n4 is any natural number from 2 to 5.

6. The redox polymer according to claim 1, characterized in that X has the structure shown in the following formula (4): Wherein, R1, R2, R3, R4, R5 and R6 are the same or different and are independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino.

7. The redox polymer according to claim 1, characterized in that X has the structure shown in the following formula (5): Among them, R7, R8, R9, R 10 , R 11 , R 12 and R 13 are the same or different and are each independently selected from hydrogen, methyl, methoxy, trifluoromethyl or amino.

8. The redox polymer according to claim 1, characterized in that A2 and X are covalently bonded by dehydration condensation, and have a structure shown in formula (6): Wherein, n5 is the number of hydrocarbon chains between the amide bond and A2, and is any natural number from 1 to 10; n6 is the number of hydrocarbon chains between the amide bond and X, and is any natural number from 1 to 10.

9. The redox polymer according to claim 1, characterized in that The structure of the redox polymer is one of the following structures:

10. A method for preparing a redox polymer, characterized in that: reacting a nitrogen-containing heterocyclic compound with a quaternary ammonium salt compound or a zwitterionic compound to generate a first polymer, wherein the nitrogen-containing heterocyclic compound is selected from any one of 4-vinylpyridine and N-vinylimidazole; The metal complex X is grafted onto the first polymer to obtain a redox polymer as shown in the following formula (1): in, A1 and A2 are the same and are selected from any one of 4-vinylpyridine and N-vinylimidazole, A3 is the quaternary ammonium salt compound or the zwitterionic compound, The metal complex X has a structure as shown in the following formula (2): in, M is a transition metal, L1, L2, L3, L4, L5 and L6 are nitrogen-containing heterocyclic ligands, and they are combined in pairs to form three bidentate ligands; n1, n2 and n3 are the same or different and are any natural number between 100 and 1000.